2023
DOI: 10.1021/acsearthspacechem.2c00270
|View full text |Cite
|
Sign up to set email alerts
|

Suspension of Crustal Materials from Wildfire in Indonesia as Revealed by Pb Isotope Analysis

Abstract: Southeast Asia experiences recurring wildfire events. Aerosol particles from these wildfires include metal species, which are suggested to have critical influences on the environment and climate. However, the mechanisms for emission of these elements from the wildfires in the region remains unclear. We analyzed both the elemental composition and the isotope ratios of lead (Pb), which is an environmentally important element. Our samples were collected in Singapore as the total suspended particulate (TSP) matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Detailed characteristics of the observation site are provided in our previous publications (Budisulistiorini et al., 2017, 2018; Chen et al., 2018; Das et al., 2023; Yang et al., 2021). Briefly, Singapore is closely located to the tropical peatland in Indonesia, including the ones in Sumatra and Kalimantan islands (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed characteristics of the observation site are provided in our previous publications (Budisulistiorini et al., 2017, 2018; Chen et al., 2018; Das et al., 2023; Yang et al., 2021). Briefly, Singapore is closely located to the tropical peatland in Indonesia, including the ones in Sumatra and Kalimantan islands (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…In the following, these observation periods will be called as "2015 October," "2018 October," "2019 April," and "2019 September-October," respectively. Detailed characteristics of the observation site are provided in our previous publications (Budisulistiorini et al, 2017(Budisulistiorini et al, , 2018Chen et al, 2018;Das et al, 2023;Yang et al, 2021). Briefly, Singapore is closely located to the tropical peatland in Indonesia, including the ones in Sumatra and Kalimantan islands (Figure 1).…”
Section: Observation Sitementioning
confidence: 99%
“…Third, Pb released into the atmosphere from wildfires in southeast Asia and Australia may have been transported by seasonal and easterly winds and deposited into the Indian Ocean. Das et al [41] determined that the ratios of Pb isotopes ( 208 Pb/ 207 Pb and 206 Pb/ 207 Pb) increased during wildfire haze periods in Indonesia, and suggested that the suspension of the crustal material was the dominant emission source of total suspended particulate (TSP) matter. Fourth, it could be the result of the additional dissolution of particulate Pb from the artificial origin (i.e., especially fine particulate forms smaller than 50 µm, which are dissolved very efficiently), which is continuously introduced to the water column on the way to being exported to the deeper layer.…”
Section: Distribution Of Radioactive 210 Pb In the Indian Oceanmentioning
confidence: 99%